Realisasi Strategi Kesantunan dalam Wacana Dakwah - Saefudin Saefudin (Buletin Al-Turas, 2017)
AbstractThe research dealing with the speech acts and politeness strategy in the texts of religius speech/Khutbah Jum’at aims at describing the kinds of illocutionary speech acts and politeness strategy used by da’i in making speech text or discourse. The method used in the reasearch is qualitative and descriptive method. This researh is a contectual one by deciding the research components. The speech acts study is mainly based on the searle’s theory, and the other suppoting theories, especilaly related to the functional language theory. The data is taken from the collection of Islamic speeh, which were published by Masjid Agung Sunda Kelapa Jakarta. Furthermore, based on the analysis, the data  found in the texts involve speech acts modes, kinds of illocitionary speech acts, and the politeness strategy as well.. However, the meaning or massage implied in the texts is still informative expressions, but not able to touch an important aspect of the other different speech acts and the politeness strategies suitable to the context of situation and culture.     AbstrakPenelitian tentang kesantunan berbahasa pada teks ceramah/khutbah Jumat ini bertujuan untuk menjelaskan jenis tindak tutur ilokusi dan strategi kesantunan yang digunakan oleh penceramah/khotib dalam pembuatan teks atau wacana ceramah/khutbahnya. Metode penelitian yang digunakan adalah metode kualitatif yang bersifat deskriptif. Penelitian ini bersifat kontekstual dengan mempertimbangan komponen tutur. Kajian tindak tutur berlandaskan pada teori J.L Austin dan Searle, serta teori-teori pendukung lainnya, terutama yang terkait dengan bahasa fungsional. Data diambil dari kumpulan ceramah/khutbah Jum’at yang diterbitkan oleh Masjid Agung Sunda Kelapa. Berdasarkan hasil analisis dan pemaparan data-data yang ditemukan dalam wacana ceramah/khotbah Jum’at meliputi; modus tuturan, jenis tuturan ilokusioner, serta strategi kesantunan. Namun demikian, pesan yang terkandung dalam teks ceramah/Khutbah Jum’at masih bersifat informatif, belum sampai menyentuh persoalan pentingnya tindak tutur yang lain dan strategi kesantunan sesuai dengan konteks situasi dan budaya. DOI: 10.15408/al-turas.v23i1.5159